A Refamilialized System? An Analysis of Recent Developments of Personal Assistance in Sweden - Rauch, Dietmar; Olin, Elisabeth; Dunér, Anna (2018)
The Swedish system of disability support is often praised for its comparably well-developed Personal Assistance (PA) scheme. PA is formally prescribed as a social right for disabled people with comprehensive support needs in the Act Concerning Support and Services to Persons with Certain Functional Impairments (LSS). In the decade following the introduction of LSS in 1994, the PA-scheme expanded steadily to accommodate the support needs of more and more disabled people. It is commonly believed that the expansion of PA has substantially boosted the agency of both disabled people and their relatives. This article critically discusses in what direction the Swedish system of disability support has moved in the past decade. Is the common image of a system moving towards an ever increasing defamilialization of disability support still accurate? Or are there signs of stagnation, or even reversal towards refamilialization? What are the possible consequences of the more recent developments for disabled people and their relatives in terms of agency and equality? These questions will be discussed with the help of an analysis of the regulatory framework of disability support, statistical data and findings from public reports.
Keywords: Sweden; Agency; assistance allowance; defamilialization; disability support; Equality; familialism; personal assistance